Cohesive Devices in Translator Training: A Study Based on a Romanian Translational Learner Corpus - Arhire, Mona (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
Formal links are naturally associated with cohesion as one of the main features of discourse. Cohesion has been extensively discussed in the literature especially in terms of the mechanisms generating it, but also in terms of its equivalence in translation. As with any type of discourse, the communicative value of translated texts is enhanced by their cohesive texture. Less attention has been granted to the translation of formal links carrying additional functions though. This study examines some cohesive devices in student translations with a special focus on the translatability of ellipsis, substitution and reference when they are enriched with stylistic, sociolectal and rhetorical values. The study is based on a translational learner corpus consisting of Romanian graduate students’ translations of a short story from English into Romanian. The methodology for assessing and analyzing the learner corpus is of both quantitative and qualitative nature and employs simplification, explicitation and neutralization. The conclusions comprise insights into some problematic areas in the trainees’ translations, as well as observations related to contrastive aspects of cohesive devices between English and Romanian. A teaching methodology is subsequently derived from the findings in an attempt to offer a more comprehensive approach to the pedagogy of translating cohesive devices with stylistic load.